Gender and Islam through Leila Ahmed’s Lens: Methodology, Social Realities, and Personal Insights: - Hafizah, Yulia (Pusat Studi Gender dan Anak Universitas Islam Negeri Antasari Banjarmasin, 2024)
The study on women and gender in Islam has become an intriguing subject for many scholars over the past few decades. One of these is Leila Ahmed's work entitled